1999
DOI: 10.1002/(sici)1097-0061(19990630)15:9<793::aid-yea415>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a centromere binding factor 3d (CBF3D) gene fromCandida glabrata

Abstract: The gene encoding centromere binding factor 3d (CBF3D) of the human pathogenic yeast Candida glabrata has been isolated by hybridization of Saccharomyces cerevisiae CBF3D (ScCBF3D) DNA to a C. glabrata partial genomic library. Sequence analysis revealed a 540 bp open reading frame encoding a protein of 179 amino acids with a calculated molecular mass of 20·9 kDa. The amino acid sequence is highly homologous (78·6% identity) to ScCbf3d and 48·3% identical to the human homologue p19 (SKP1). Southern blot analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Thus, it was of interest to determine whether the inner kinetochore protein homologs are species specific. Based on the ability of an Scskp1 deletion strain containing CgSKP1 on a LEU2-bearing plasmid to grow on 5-FOA (which means that the ScSKP1 gene on a URA3-bearing plasmid can be lost), CgSkp1p was previously shown to complement an Scskp1⌬ mutant (60). To determine whether the other C. glabrata inner kinetochore proteins could complement deletions of the corresponding genes in S. cerevisiae, we inserted the C. glabrata genes under the control of their own promoters into plasmids that contained either an ScLEU2 or an ScHIS3 marker and tested them in the corresponding S. cerevisiae deletion strains (plasmids pRSCg1, pTS32, pTS39, pTS37, pRSCg3D, and pTS34) ( Table 1; see also Table S1 in the supplemental material for plasmid constructs).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it was of interest to determine whether the inner kinetochore protein homologs are species specific. Based on the ability of an Scskp1 deletion strain containing CgSKP1 on a LEU2-bearing plasmid to grow on 5-FOA (which means that the ScSKP1 gene on a URA3-bearing plasmid can be lost), CgSkp1p was previously shown to complement an Scskp1⌬ mutant (60). To determine whether the other C. glabrata inner kinetochore proteins could complement deletions of the corresponding genes in S. cerevisiae, we inserted the C. glabrata genes under the control of their own promoters into plasmids that contained either an ScLEU2 or an ScHIS3 marker and tested them in the corresponding S. cerevisiae deletion strains (plasmids pRSCg1, pTS32, pTS39, pTS37, pRSCg3D, and pTS34) ( Table 1; see also Table S1 in the supplemental material for plasmid constructs).…”
Section: Resultsmentioning
confidence: 99%
“…In previous work, two of the inner kinetochore proteins of C. glabrata, Skp1p and Cbf1p (CgSkp1p and CgCbf1p, respectively), were cloned and characterized (60,61). CgSkp1p is 76% identical to and functionally exchangeable with the S. cerevisiae homolog.…”
mentioning
confidence: 99%
“…The multiprotein complex Cbf3 binds to CDEIII and consists of the proteins Cbf3a, Cbf3b, Cbf3c and Cbf3d (Stemmann and Lechner, 1996). The only centromeric protein that was cloned from human pathogenic yeasts is Cbf3d from C. glabrata (Stoyan et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have cloned a CBF3d homolog from C. glabrata and showed that it can functionally substitute for its S. cerevisiae counterpart (57). In this study we present the cloning and functional characterization of the CBF1 gene of C. glabrata (CgCBF1).…”
mentioning
confidence: 99%